Premature ageing of the immune system relates to increased anti‐lymphocyte antibodies (ALA) after an immunization in HIV‐1‐infected and kidney‐transplanted patients. (6th October 2013) - Cagigi, A.; Rinaldi, S.; Santilli, V.; Mora, N.; C. Manno, E.; Cotugno, N.; Zangari, P.; Aquilani, A.; Guzzo, I.; Dello Strologo, L.; Rossi, P.; Palma, P.
Summary Low‐affinity immunoglobulin (Ig)G with potential autoreactivity to lymphocytes and hypergammaglobulinaemia have been described previously in HIV‐1‐infected patients. Whether such antibodies increase after challenging the immune system, for example with an immunization, is not known. In the present study, the modulation of antibodies with low affinity and potential autoreactivity was evaluated after 2012–13 seasonal flu vaccination with a simple empirical laboratory test measuring the titres of anti‐lymphocyte antibodies (ALA) in two different models of secondary immunodeficiency: HIV‐1 vertically infected patients (HIV) and patients treated with immunosuppressive therapies after kidney transplantation (KT) compared to healthy individuals (HC). In parallel, the activation status of B cells and their degree of immune senescence was evaluated by measuring the B cell interleukin (IL)‐21R expression/plasma IL‐21 levels and the frequencies of mature‐activated (MA) and double‐negative (DN) B cells. A significant increase of ALA titres was observed after vaccination in HIV and KT but not in HC, and this correlated directly with the frequencies of both MA and DN and inversely with the B cell IL‐21R expression. This suggests that the quality of an immune response triggered by flu vaccination in HIV and KT may depend upon the activation status of B cells and on their degree of immune senescence. Further investigations are needed to verify whether high frequencies of MA and DN may also relate to increase autoimmunity after immunization in high‐risk populations.